2021
DOI: 10.1111/head.14210
|View full text |Cite
|
Sign up to set email alerts
|

Persistent posttraumatic headaches and functioning in veterans: Injury type can matter

Abstract: Objective To characterize the relationship between head trauma types (blast injury, blunt injury, combined blast+blunt injury) with subsequent headache presentations and functioning. Background Posttraumatic headaches (PTHs), the most common sequelae of traumatic brain injury (TBI), are painful and disabling. More than 400,000 veterans report having experienced a TBI, and understanding the predictors of PTHs may guide treatment developments. Methods This study used a nested‐cohort design analyzing baseline dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…To date, however, most reports find no evidence that blast injury and DHT produce significantly different outcomes for STBI 3,26,41 . One recent study found minimal differences 42 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…To date, however, most reports find no evidence that blast injury and DHT produce significantly different outcomes for STBI 3,26,41 . One recent study found minimal differences 42 …”
Section: Discussionmentioning
confidence: 97%
“…They found headache was more common in those with LOC (p < 0.05) and memory problems were more common in those with no LOC.Couch and Stewart in a smaller study dealing with headache found no difference between those with blast or DHT 26. A recent study by Nabity et al reported worse headache with blast injury, however, the odds ratios were not statistically significantly different 42.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In the article "Persistent posttraumatic headaches and functioning in Veterans: Injury type can matter," study subjects were enrolled in a randomized controlled trial of cognitive behavior therapy for the treatment of posttraumatic headache. 1 The current study was designed to test three hypotheses: (1) to determine the landscape of this population of injured veterans presenting for care where injury mechanisms were categorized into three groups Blast, Blunt, and both;…”
Section: The Road Takenmentioning
confidence: 99%
“…In the article “Persistent posttraumatic headaches and functioning in Veterans: Injury type can matter,” study subjects were enrolled in a randomized controlled trial of cognitive behavior therapy for the treatment of posttraumatic headache 1 …”
mentioning
confidence: 99%